Antithrombotic therapy and clinical outcomes at 1 year in the Spanish cohort of the EORP‐AF Long‐term General Registry. (17th November 2021) - Pérez Cabeza, Alejandro I.; Rivera‐Caravaca, José Miguel; Roldán‐Rabadán, Inmaculada; García Seara, Javier; Bertomeu‐Gonzalez, Vicente; Leal, Mariano; García‐Fernandez, Amaya; Tercedor Sanchez, Luis; Ayarra, Maite; Ciudad, Marianela; Castaño, Sara; Maestre, Ana; et al.
Abstract: Background: Atrial fibrillation (AF) increases the risk of thromboembolism. We investigate the efficacy and safety of oral anticoagulation (OAC) therapy and explored the number needed to treat for net effect (NNTnet) of OAC in the Spanish cohort of the EURObservational Research Programme‐AF (EORP‐AF) Long‐term General Registry. Methods: The EORP‐AF General Registry is a prospective, multicentre registry conducted in ESC countries, including consecutive AF patients. For the present analysis, we used the Spanish cohort, and the primary outcome was any thromboembolism (TE)/acute coronary syndrome (ACS)/cardiovascular death during the first year of follow‐up. Results: 729 AF patients were included (57.1% male, median age 75 [IQR 67–81] years, median CHA2 DS2 ‐VASc and HAS‐BLED of 3 [IQR 2–5] and 2 [IQR 1–2], respectively). 548 (75.2%) patients received OAC alone (318 [43.6%] on VKAs and 230 [31.6%] on DOACs). After 1 year, the use of OAC alone showed lower rates of any TE/ACS/cardiovascular death (3.0%/year; p  < 0.001) compared to other regimens, and non‐use of OAC alone (HR 4.18, 95% CI 2.12–8.27) was independently associated with any TE/ACS/cardiovascular death. Balancing the effects of treatment, the NNTnet to provide an overall benefit of OAC therapy was 24. The proportion of patients on OAC increased at 1 year (87% to 88.1%), particularly on DOACs (33.6% to 39.9%) ( p  = 0.015), with low discontinuation rates. Conclusions: In this contemporary cohort of AF patients, OAC therapy was associated with better clinical outcomes at 1 year and positive NNTnet. OAC use slightly increased during the follow‐up, with low discontinuation rates and higher prescription of DOACs.